Taxonomic and bionomic notes on Arma chinensis (Fallou) - Zou, Deyu; Wang, Mengqing; Zhang, Lisheng; Zhang, Ying; Zhang, Xiaojun; Chen, Hongyin (Zootaxa, 2012)
The male genitalia and other important morphological characters of Arma chinensis are redescribed and illustrated. Some bio-logical characters of this stink bug, such as the predatory behavior, mating, oviposition, hatching, molting, emergence, colonization, and cannibalism are noted.